2014
DOI: 10.1093/brain/awu026
|View full text |Cite
|
Sign up to set email alerts
|

Leukoencephalopathy with brainstem and spinal cord involvement and lactate elevation: clinical and genetic characterization and target for therapy

Abstract: Leukoencephalopathy with brainstem and spinal cord involvement and lactate elevation is a disorder caused by recessive mutations in the gene DARS2, which encodes mitochondrial aspartyl-tRNA synthetase. Recent observations indicate that the phenotypic range of the disease is much wider than initially thought. Currently, no treatment is available. The aims of our study were (i) to explore a possible genotype-phenotype correlation; and (ii) to identify potential therapeutic agents that modulate the splice site mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 29 publications
2
88
1
1
Order By: Relevance
“…6 Infantile onset with severe disease course is rare in LBSL. MRI in these cases shows diffuse supratentorial white matter abnormalities, reminiscent of those seen in HBSL, 7,8 whereas in most LBSL cases, supratentorial signal changes are focal. 2,8 The intraparenchymal trajectories of the trigeminal nerves and mesencephalic trigeminal tracts are typically affected in LBSL, 2 but normal in HBSL.…”
mentioning
confidence: 77%
“…6 Infantile onset with severe disease course is rare in LBSL. MRI in these cases shows diffuse supratentorial white matter abnormalities, reminiscent of those seen in HBSL, 7,8 whereas in most LBSL cases, supratentorial signal changes are focal. 2,8 The intraparenchymal trajectories of the trigeminal nerves and mesencephalic trigeminal tracts are typically affected in LBSL, 2 but normal in HBSL.…”
mentioning
confidence: 77%
“…It is worth mentioning that the two patient-derived skin fibroblasts are heterozygous compounds and contain a missense mutation and a splicing defect. The splicing defect in the case of a DARS2 -related LBSL patient was reported to be leaky and to allow the production of a significant amount of WT protein (13, 14). The same authors have further demonstrated the cell-type dependence of splicing of mt-AspRS mRNA and that the mutations have a larger effect on exon 3 exclusion in neuronal cell lines than in non-neural cell lines (57).…”
Section: Discussionmentioning
confidence: 99%
“…LBSL is a progressive neurodegenerative disorder that affects the brain white matter, and leads mostly to abnormal muscle stiffness and difficulties with coordinating movements. Most affected patients eventually require wheelchair assistance (14). Mutations within RARS2 , the gene coding for the mitochondrial arginyl-tRNA synthetase (mt-ArgRS), are correlated with pontocerebellar hypoplasia type 6 (PCH6) (15).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some common pathogenic alleles can be missed by conventional sequencing approaches, including targeted NGS, unless methods are specifically adapted or additional assays are included to capture them. These can include deep intronic splice variants as in leukoencephalopathy with brainstem and spinal cord involvement and lactate elevation (van Berge et al , 2014) or whole gene deletions and duplications as in Pelizaeus-Merzbacher disease (Lee et al , 2006). …”
Section: Discussionmentioning
confidence: 99%